(untitled) (Sri Lanka Journal of Indigenous Medicine (SLJIM), 2023)
Shitada (Gingivitis), a Dantamulagataroga of varying severities is nearly universal. Acharya Sushruta has mentioned including Gandusha, a Pratisarana in the management of Shitada. This study mainly focused to compare the efficacy of Triphaladi kwatha gandusha, Priyangavadi churna pratisarana and Triphala churna orally in the management of Shitada (Gingivitis) and the treatment period is one month. In this clinical trial, 32 patients were registered and all the patients completed the treatment. In Group A, 16 patients had been prescribed Triphaladi kwatha gandusha, Priyangavadi churna pratisarana and Triphala churna orally and in Group B, 16 patients had been prescribed Triphaladi kwatha gandusha and Priyangavadi churna pratisarana. The assessment was done on the basis of signs and symptoms i.e. Akasmata Rakta Srava (Bleeding), Shotha (Inflammation), Krishnata (Discoloration of gums), Mukha daurgandhya (Halitosis), Vedana (Pain), Dantamamsa prakledata (Moistness), Paka (Pus discharge), Dantamamsa mriduta (Sponginess), Gingival Index and Bleeding Index. The results showed that complete remission was observed in 31.25% and 6.25% of patients in groups A and B, respectively. The study concludes that the administration of Triphaladi kwatha gandusha, Priyangavadi churna pratisarana and Triphala churna orally is more effective in the management of Shitada (Gingivitis).